Ecosystem engineering impact of Limnoperna fortunei in South America - Darrigran, Gustavo Alberto (2011)
Limnoperna fortunei, or golden mussel, has invaded aquatic ecosystems in the Americas following it introduction from Southeast Asia. It is not only an aggressive invasive species, it is also a very effective ecosystem engineer, altering both ecosystem structure and function, and causes great ecological and economic impacts. This paper describes its impact as an ecosystem engineer (on benthic communities and the water column). A review of the existing scientific literature is presented, and the impact and the mechanisms by which the golden mussel modifies, maintains, and creates new environmental conditions in the invaded South American inland freshwater environments are analyzed. Understanding the ecosystem engineering roles of L. fortunei is important for its management and/or control in the invaded areas, and in cases of future invasions.